Good Corporate Governance, Job Motivation, Organization Culture Which Impact Company Financial Performance - Putu Han Widiatmika; Gede Sri Darma (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis purpose of the study is to analyze the effect of transparency,accountability, responsibility,independency,fairness, work motivation, organization cultureand good corporate governance towards financial performance. This study applied a quantitative approach at rural banks in Badung regency. The method ofcollecting data applied questionnaires. The total population in this study were 52 rural banks located in Badung Regency. The sampling technique applied purposive sampling with the purpose of getting a representative sampleaccordance with the specified criteria and the data analysis techniques applied path analysis.The results of thestudy by path analysis defined the transparency, accountability, responsibility, independency and fairness have a significant effect on GCG. GCG has a significant effect on financial performance and work motivation affects financial performance. Organizational culture has a significant effect on financial performance. Company financial performance variable influenced by GCG, motivation and organizational culture. From this study, can be concluded that the application of GCG principles, work motivation, and organizational culture very influential on the financial performance of rural banks in Badung Regency.The limitations of this study are limited in examining the variables of Good Corporate Governance, motivation and organizational culture. There are other variables that can also affect the company's financial performance. Suggestions for further research is try to applying othervariables which able to influence profit management practices such as managerial ownership, audit quality and profitability to determine the GCG implementation effect.